Time of Fast Learning in Speed-Accuracy Tasks is Different for Children and Adults - Kristina Motiejūnaitė; Dalia Mickevičienė; Albertas Skurvydas; Kazimieras Pukėnas; Diana Karanauskienė; Sandrija Čapkauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Motor learning is characterized by specific set of changes in performance parameters which occur gradually over a course of learning period. Research aim. The aim of the study was to establish and compare the characteristics of learning speed- accuracy movements of children and adults. Research methods. The research participants were 13 healthy boys, 16 girls, 5 healthy men and 7 women. The research was carried out applying the analyzer of dynamic parameters of human leg and arm movement (DPA-1). We registered maximal and average movement speed, the reaction time and the movement trajectory of the right hand. Research results. We established signiﬁ cant differences (p < 0.05-0.001) in reaction time (RT), average movement speed (Va), maximal movement speed (Vm) and movement trajectory (S) between children and adults. Discussion and conclusions. Motor adaptation in timescales of minutes is supported by two distinct processes: one process when a person learns slowly from errors but has strong retention, and another process is when a person learns rapidly from errors but has poor retention (Ethier et al., 2008). We might only speculate that children used the second strategy more than adults. The time of fast learning in a speed-accuracy task was different between children and adults. The accuracy was most improved by children at the expense of the quickness, while adults improved only the average velocity of their performance. Besides, most of the variability of performance variables changed more signiﬁ cantly in children than in adults. Keywords: motor learning, motor control, age, manual task.